2021
DOI: 10.3390/catal11101233
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing MgO Content for Boosting γ-Al2O3-Supported Ni Catalyst in Dry Reforming of Methane

Abstract: The dry reforming of methane (DRM) process has attracted research interest because of its ability to mitigate the detrimental impacts of greenhouse gases such as methane (CH4) and carbon dioxide (CO2) and produce alcohols and clean fuel. In view of this importance of DRM, we disclosed the efficiency of a new nickel-based catalyst, which was promoted with magnesia (MgO) and supported over gamma-alumina (g-Al2O3) doped with silica (SiO2), toward DRM. The synthesized catalysts were characterized by H2 temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…Rosdin et al [92] evaluated various oxide supports for the DRM reaction, including Al 2 O 3 , Al 2 O 3 -ZrO 2 , and Al 2 O 3 -MgO, and the results indicated that Ni/Al 2 O 3 -MgO showed the best stability and activity as well as the least coke formation. Bagabas et al [93] found that MgO content significantly affected the γ-Al 2 O 3 -supported Ni catalyst for the resistance to coke deposition. Zeng et al [94] reported a mesoporous Ni/MgO-mSiO 2 catalyst; alkaline oxidized magnesium not only inhibits the sintering and deactivation of Ni at high temperatures but also promotes the cracking of CH 4 and the activation of CO 2 at the "Ni-MgO" interface formed in mSiO 2 , thereby eliminating carbon deposition.…”
Section: Oxide-supported Catalystsmentioning
confidence: 99%
“…Rosdin et al [92] evaluated various oxide supports for the DRM reaction, including Al 2 O 3 , Al 2 O 3 -ZrO 2 , and Al 2 O 3 -MgO, and the results indicated that Ni/Al 2 O 3 -MgO showed the best stability and activity as well as the least coke formation. Bagabas et al [93] found that MgO content significantly affected the γ-Al 2 O 3 -supported Ni catalyst for the resistance to coke deposition. Zeng et al [94] reported a mesoporous Ni/MgO-mSiO 2 catalyst; alkaline oxidized magnesium not only inhibits the sintering and deactivation of Ni at high temperatures but also promotes the cracking of CH 4 and the activation of CO 2 at the "Ni-MgO" interface formed in mSiO 2 , thereby eliminating carbon deposition.…”
Section: Oxide-supported Catalystsmentioning
confidence: 99%
“…The support's surface acidic-basic equilibrium may influence the reaction performance in several different aspects. While acidic sites favor CH 4 cracking, which leads to carbon formation [96], the increase in the support's basicity is related to an enhanced removal of carbon deposits, which may lead to higher catalyst stability [97]. Gao et al [98] indicate that such acidic-basic equilibrium on the catalyst support may also influence the electronic environment of the active sites and further favor/inhibit side reactions such as CH 4 cracking and CO disproportionation.…”
Section: Role Of Catalyst Supportmentioning
confidence: 99%
“…On the other hand, excessive basicity may also lead to carbon deposition, decrease metal dispersion, lead to lower H 2 /CO ratios and compromise the overall catalyst performance [98,100]. Bagabas et al [97] investigated the optimization of the MgO content on Al2O3-supported Ni catalysts for DRM and reported that the highest H 2 /CO = 0.95 (T = 800 • C, X CH 4 = 86%, X CO 2 = 91%) was obtained with 2.0 wt% MgO, while higher contents were actually detrimental for the process.…”
Section: Role Of Catalyst Supportmentioning
confidence: 99%